Genetic differences between Helicobacter pylori strains isolated from patients with chronic mild and severe gastritis - E. V. Golubkina; V. M. Sorokin; B. N. Levitan; A. R. Umerova; N. V. Kamneva (Антибиотики и Химиотерапия)
Background. Helicobacter pylori-associated chronic gastritis (CG), being a very heterogeneous group, still does not have a divisin based on Helicobacter pylori (Hp) genotyping data, which could predict the clinical form of CG.The aim of the study is to search for the prevalence of the cagA gene or any allelic combination of the vacA gene, or stable combinations of cagA and any allelic combination of vacA genes in Hp isolates from patients with mild and severe CG, as well as patients with peptic ulcer disease (PUD).Methods. Hp isolates from gastrobiopsy specimens were genotyped for cagA and vacA allelic combinations (s1m1, s2m1, s1m2, s2m2). The difference in the occurrence of vacA allelic combinations was assessed by Mann–Whitney U test; the conjunction of cagA and vacA allelic combinations was assessed by the Spearman's rank correlation coefficient (rs).Results. The cagA gene was found in more than half of all cases, both in patients with ulcer and in patients with CG (mild and severe). The incidence of vacAs1m1 (the most virulent allelic combination) showed no significant differences in all forms of gastritis and in PUD; the correlation between cagA and vacAs1m1 was significant in all groups of patients, rs ranged from 0.57 to 0.72. In patients with mild CG, an abundance of non-virulent allelic combination vacAs2m2 was observed, which was significantly different from its occurrence both in patients with severe CG and in patients with ulcer; the joint occurrence of vacAs2m2 and cagA in patients with mild CG was chaotic (rs=-0.13; P=0.40).Conclusion. In mild CG, despite the absence of significant differences in cagA and vacAs1m1 (when compared with severe CG and ulcer disease), strains with a non-virulent allelic combination vacAs2m2 were significantly dominant; therefore, the detection of this particular allelic combination of vacA speaks in favor of a mild course of CG.